2020
DOI: 10.1159/000510470
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nrf2 in D-Galactose-Induced Cardiac Aging in Mice: Involvement of Oxidative Stress

Abstract: <b><i>Introduction:</i></b> Cardiac aging is the major risk factor for advanced heart disease, which is the leading cause of death in developed countries, accounting for &#x3e;30% of deaths worldwide. <b><i>Objective:</i></b> To discover the detailed mechanism of cardiac aging and develop an effective therapeutic candidate drug to treat or delay cardiac aging. <b><i>Methods:</i></b> We used D-galactose to induce cardiac aging in Nrf2&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Rac-1 and protein carbonyl (PC) level also increased after Dgalactose injection. 36,38 Nrf2, a major stress-response transcription factor, regulates the expression of heme oxygenase-1 (HO-1), Cu/ZN superoxide dismutase (SOD), Nox-2, Rac-1 and significantly reduces ageing-induced oxidative stress in D-galactose-induced ageing rat hearts. 36 The activation of nitric oxide synthases (NOS) and nitric oxide (NO) production triggers the production of O 2 and OH-free radicals, leading to cell damage.…”
Section: Effec Tofd -G Al Ac Tos E Adminis Tr Ationonc Ardiacoxidativ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Rac-1 and protein carbonyl (PC) level also increased after Dgalactose injection. 36,38 Nrf2, a major stress-response transcription factor, regulates the expression of heme oxygenase-1 (HO-1), Cu/ZN superoxide dismutase (SOD), Nox-2, Rac-1 and significantly reduces ageing-induced oxidative stress in D-galactose-induced ageing rat hearts. 36 The activation of nitric oxide synthases (NOS) and nitric oxide (NO) production triggers the production of O 2 and OH-free radicals, leading to cell damage.…”
Section: Effec Tofd -G Al Ac Tos E Adminis Tr Ationonc Ardiacoxidativ...mentioning
confidence: 99%
“…39 Previous studies have shown that D-galactose treatment significantly increases the levels of NO and iNOS. 22,[37][38][39][40] The antioxidant enzyme system is an antioxidant system and includes SOD, catalase (CAT), glutathione peroxidase (GSH-Px)…”
Section: Effec Tofd -G Al Ac Tos E Adminis Tr Ationonc Ardiacoxidativ...mentioning
confidence: 99%
See 3 more Smart Citations